1982
DOI: 10.1097/00000658-198206000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia

Abstract: This report concerns evaluation of patient-controlled analgesia (PCA) in the form of two preliminary investigations. In the first study, the patient-controlled analgesia device, which consists of a pump linked to a timer so that patients can activate intravenous administration of morphine sulfate to themselves during the postoperative period, was used in seven morbidly obese patients. The amount of morphine used during the first 36 hours was found to vary between 32 and 185 mg, with a significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Owen et al (1990) sought to discover whether patients administered a similar amount of morphine via a PCA bolus dose, independently of a background infusion The only mention of preoperative information given to patients about the use of the PCA device m these studies was that it was given at the time of consent Information content was not disclosed The results demonstrated that, despite a standard background infusion and matching of the patients mto three groups with each group able to demand a different bolus size, no relationship between doses occurred There was no relationship between size of dose and demand rate for the first 24 hours followmg surgery This finding agrees with that of Bennett et al (1982a), and conhasts with the widely held view that patients make sufficient demands to mamtam their blood opiate concenhation above the minimum effective analgesic concentration…”
Section: Variation In Pca Demandsupporting
confidence: 62%
See 2 more Smart Citations
“…Owen et al (1990) sought to discover whether patients administered a similar amount of morphine via a PCA bolus dose, independently of a background infusion The only mention of preoperative information given to patients about the use of the PCA device m these studies was that it was given at the time of consent Information content was not disclosed The results demonstrated that, despite a standard background infusion and matching of the patients mto three groups with each group able to demand a different bolus size, no relationship between doses occurred There was no relationship between size of dose and demand rate for the first 24 hours followmg surgery This finding agrees with that of Bennett et al (1982a), and conhasts with the widely held view that patients make sufficient demands to mamtam their blood opiate concenhation above the minimum effective analgesic concentration…”
Section: Variation In Pca Demandsupporting
confidence: 62%
“…The area of stmctured preoperahve teachmg of pahents m the use of PCA devices and what is expeded of them needs further mveshgahon The implications m terms of reduced analgesic consumphon and improved well-bemg refleded m a reduced expenenc* of postoperahve pam cannot be exaggerated to both the nurse and the patient Summary of selected researdi findings Bennett et al (1982a) A wide vanation in drug use via PCA Owen et al (1990) Pahents do not make suffiaent demands of a P C A to maintam a mimmum effechve analgesic concentrahon Rogers et al (1990) High PCA drug use, compared to tradihonal regimes Sechzer (1971) High demand for analgesic via PCA ummediately post surgery Snwatanakul et al (1983) Nurses administer less than maximum prescnbed analgesic…”
Section: Loeus Of Eontrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of PCA The considerable body of literature regarding PGA (for example, Slattery et al 1983, Tamsen 1985, Notcutt & Morgan 1990, Thomas et al 1990, Thomas 1991 confiims that supenor analgesia can be provided This is due to the fact that PGA overcomes the problem of marked differences m the pharmacokmetics and pharmacodynamics of narcotics in individual patients Because they are able to maintain a near constant level of narcotic, patients avoid penods of severe pam and sedation that come with the peaks and troughs of narcotic level m the traditional p r n protocol Glimcal benefits of PGA also include fewer respiratory complications (Bennett et al 1982), earlier ambulation (Bollish et al 1985) and a reduction m the length of post-operative hospitahzation (Keen-Szanto 1984, Glark ef a/ 1989, Thomas et ai 1990, Thomas 1991 However, successful use of PGA also depends on psychological vanables such as locus of control, coping style and levels of anxiety which can mfiuence the patient's ability to press the button, l e self-administer pam medication (see Thomas 1991 for a fuller discussion)…”
Section: Patients' Attitudes To Pain Controlmentioning
confidence: 99%
“…Pain from chest drains and surgical incisions has been cited by 45% of cardiac surgical addition, nurses' assessment of pain will influence their own practice in administering analgesics. Therefore it is patients as the worst memory of their stay in ICU (Paiement et al 1979). Suction of the ET tube has been shown to important to establish not only how accurate nurses are in assessing patients' pain in this environment but also the cause distress (Paiement et al 1979) and to increase the severity of incisional pain (Puntillo 1990).…”
Section: Pain In the Critically Ill Patientmentioning
confidence: 99%